A strategic evaluation of BIM-driven information management in the Turkish AEC industry - Kaya, Uğur (Graduate School, 2025)
This research study presents an in-depth evaluation of BIM-driven information management processes between project stakeholders in the context of the ISO 19650-2 standard. The study aimed to understand and evaluate the existing mechanisms and the recommended activities and tasks of collaborative project information management, particularly as the Turkish AEC organizations are currently implementing the ISO 19650-2 standard for information management tasks and procedures. The study employed a qualitative research design using a theoretical framework based on the derived concepts and information management stages from the ISO 19650 standard, part 2. Semi-structured interviews were conducted with purposefully selected industry representatives. The responses were transcribed, and framework analyses were made with MAXQDA through conceptual coding to identify current drivers, challenges, and incentives for BIM-driven information management. To validate the research framework, interviews were grouped into two sets. The first 12 participants were initially analyzed, and their results were compared with the second-turn analysis of the remaining 3 participants for saturation check. The frequencies of common themes, required tasks, and semantic relationships were reported systematically and interpreted to provide a conceptual implementation map, information management assignment matrix, practical insights, and actionable recommendations. Results from the qualitative framework analysis and the participant responses encompass strategies for establishing new tasks, protocols, and procedures to uphold business value by aligning information production standards with evolving project requirements, providing detailed and responsive EIRs for stakeholders, early use of CDEs, standard compliant production methods, clarity of roles and responsibilities, organizational improvements, increased capacity and capabilities, production quality and planning aligned with MIDPs, and leveraging lessons learned for enhanced information management processes. The study provides evidence-based arguments and strategic insights for BIM-driven information management processes, specifically focusing on the current implementation compatibility with the ISO 19650-2 standard. Findings and discussions highlight the necessity of industry-wide transformations, reengineered activities/tasks, and compliant information flows. These are crucial for adopting ISO 19650-2 effectively and improving information management efficiency in the AEC practice through standardized BIM tasks and procedures.
Türk inşaat endüstrisinde BIM odakli enformasyon yönetiminin stratejik değerlendirmesi
Thesis (Ph.D.) -- Istanbul Technical University, Graduate School, 2024
Keywords: information models; bilgi modelleri; BIM; BİM; construction industry; inşaat sektörü